1992
DOI: 10.1111/j.1468-2958.1992.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretations, Evaluations, and Consequences of Interpersonal Touch

Abstract: Key elements of an expectancy violations (EV) framework are forwarded as a possible organizingframeworkfir understanding how touch functions in interpersonal wmmunication. Central to applying an EVframework to touch is assessing the expectedness, interpretations, and evaluations of touch and its influence on such communication outcomes as evaluations ofcommunicatorattractiwnessand credibility. Toaddress these considerations, an experiment required participants toengage in dyadic problem-solving discussions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 43 publications
2
66
1
2
Order By: Relevance
“…This effect is referred to as the Midas touch: a brief, casual touch (often at the hand or arm) that is not necessarily consciously perceived named after king Midas from Greek mythology who had the ability to turn everything he touched into gold. For example, a half-second of hand-to-hand touch from a librarian fostered more favorable impressions of the library (Fisher et al 1976), touching by a salesperson increased positive evaluations of the store (Hornik 1992), and touch can also boost the attractiveness ratings of the toucher (Burgoon et al 1992). Recipients of such "simple" Midas touches are also more likely to be more compliant or unselfish: willing to participate in a survey (Guéguen 2002) or to adhere to medication (Guéguen et al 2010), volunteering for demonstrating in a course (Guéguen 2004), returning money left in a public phone (Kleinke 1977), spending more money in a shop (Hornik 1992), tipping more in a restaurant (Crusco and Wetzel 1984), helping with picking-up dropped items (Guéguen and Fischer-Lokou 2003), or giving away a cigarette (Joule and Guéguen 2007).…”
Section: Touch As a Behavior Modulatormentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is referred to as the Midas touch: a brief, casual touch (often at the hand or arm) that is not necessarily consciously perceived named after king Midas from Greek mythology who had the ability to turn everything he touched into gold. For example, a half-second of hand-to-hand touch from a librarian fostered more favorable impressions of the library (Fisher et al 1976), touching by a salesperson increased positive evaluations of the store (Hornik 1992), and touch can also boost the attractiveness ratings of the toucher (Burgoon et al 1992). Recipients of such "simple" Midas touches are also more likely to be more compliant or unselfish: willing to participate in a survey (Guéguen 2002) or to adhere to medication (Guéguen et al 2010), volunteering for demonstrating in a course (Guéguen 2004), returning money left in a public phone (Kleinke 1977), spending more money in a shop (Hornik 1992), tipping more in a restaurant (Crusco and Wetzel 1984), helping with picking-up dropped items (Guéguen and Fischer-Lokou 2003), or giving away a cigarette (Joule and Guéguen 2007).…”
Section: Touch As a Behavior Modulatormentioning
confidence: 99%
“…The meaning and appreciation of touch critically depend on its context (Collier 1985;Camps et al 2012), such as the relation between conversation partners (Burgoon et al 1992;Thompson and Hampton 2011), the body location of the touch (Nguyen et al 1975), and the communication partner's culture (McDaniel and Andersen 1998). There is no one-to-one correspondence between a touch and its meaning (Jones and Yarbrough 1985).…”
Section: Multisensory and Contextual Cuesmentioning
confidence: 99%
“…Burgoon (1992) dealt mainly with the types of handshake and the social importance of each one. Ritchmont and his collaborator McCroskey (2000) studied non verbal behaviour in the cross-cultural and international relations (Stamatis, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For males and females who held a high reward for the receiver of the message, males who employed the high gaze were rated as more dominant whereas females who employed high eye gaze were rated as more submissive. Burgoon, Walther, and Baesler (1992) found that the use of casual touch conveyed nonverbal relational messages such as greater immediacy, greater affection, trust, relaxation, similarity, and informality. The effect of touch in this study was moderated by valence of the toucher.…”
mentioning
confidence: 99%
“…Burgoon et al (1992) and Mehrabian (1969) found that nonverbal relational messages are related to attraction or liking. For example, Mehrabian (1969) concluded that eye contact increases as a person reports higher levels of attraction until the attraction level become very high.…”
mentioning
confidence: 99%